2018
DOI: 10.1002/chem.201803008
|View full text |Cite
|
Sign up to set email alerts
|

Why Do B–P and Al–P Polymers Differ? Structures, Stability, and Electronic Properties of Chain and Ring [H2PEH2]n Oligomers (E=B, Al; n=115)

Abstract: Chain and ring [H PEH ] oligomers (E=B, Al; n=2-15) have been computationally studied at the B3LYP/def2-TZVP level of theory. A strong tendency to cyclization was found for the chain Al-P oligomers with n>7, whereas analogous long B-P oligomers can exist as chain structures. Subsequent oligomerization enthalpies approach each other very closely for the ring and chain oligomers with an increase of n. However, these oligomers have very different electronic properties with band gaps below 0.2 eV for the chain [H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…This data suggests that as phosphinoborane chain grows, residual unreacted base can coordinate at the Lewis acidic boron terminus. The ability of Lewis bases to coordinate to oligomers formed in situ is consistent with recent computational studies by Pomogaeva, Timoshkin, and Scheer on phosphinoborane linear oligomer, [PH 2 ‐BH 2 ] 7 , where it was shown that the lowest unoccupied molecular orbital is localized at the boron terminus [40] . A further report on the stability of Lewis acid‐ and Lewis base adducts of analogous phosphinoborane decamers, [PH 2 ‐BH 2 ] 10 , showed that tethering of N‐heterocyclic carbenes (NHCs) to boron favors the formation of linear over cyclic species [41] .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This data suggests that as phosphinoborane chain grows, residual unreacted base can coordinate at the Lewis acidic boron terminus. The ability of Lewis bases to coordinate to oligomers formed in situ is consistent with recent computational studies by Pomogaeva, Timoshkin, and Scheer on phosphinoborane linear oligomer, [PH 2 ‐BH 2 ] 7 , where it was shown that the lowest unoccupied molecular orbital is localized at the boron terminus [40] . A further report on the stability of Lewis acid‐ and Lewis base adducts of analogous phosphinoborane decamers, [PH 2 ‐BH 2 ] 10 , showed that tethering of N‐heterocyclic carbenes (NHCs) to boron favors the formation of linear over cyclic species [41] .…”
Section: Resultssupporting
confidence: 88%
“…The ability of Lewis bases to coordinate to oligomers formed in situ is consistent with recent computational studies by Pomogaeva, Timoshkin, and Scheer on phosphinoborane linear oligomer, [PH 2 -BH 2 ] 7 , where it was shown that the lowest unoccupied molecular orbital is localized at the boron terminus. [40] A further report on the stability of Lewis acid-and Lewis base adducts of analogous phosphinoborane decamers, [PH 2 -BH 2 ] 10 , showed that tethering of N-heterocyclic carbenes (NHCs) to boron favors the formation of linear over cyclic species. [41] In contrast, the work also indicated that coordination of weaker Lewis bases (such as NH 3 ) at the boron terminus did not result in linear chains that were more stable than cyclic analogues.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…et al furnished a comprehensive account of how to transport the orbital occupation computation outcomes from Gaussian 16 software into the wave function analysis tool Multiwfn, in order to acquire discrete orbital occupation data at varying energy levels. Upon broadening with a Gaussian function, a continuous density of states (DOS) map can be generated [52].…”
Section: The Changes In the Orbital Occupation Of Each System Before ...mentioning
confidence: 99%